Immune characteristics of olfactory ensheathing cells and repair of nerve injury - Chen, Ding-yi; Zhang, Wen-jun; Zuo, Cheng; Xu, Yong-sheng; Fu, Liu-xiang (Frontiers in Immunology, 2025)
The process of nerve injury is accompanied by the change of inflammatory microenvironment, which is not conducive to axonal regeneration and hinders the repair of injured nerve. Therefore, looking for a way to improve the inflammatory attack and immune state around the injured nerve is beneficial to the progress of nerve injury repair. In recent years, cell transplantation strategy has played a foreground role in the repair of nerve injury. Olfactory ensheathing cells (OECs) are a special kind of glial cells, which have the characteristics of continuous renewal and survival, antigenic characteristics, variability and promoting the repair of nerve injury. OECs have been recognized in different injury models, including clinical trials, which has become a dominant cell in cell replacement therapy. An important feature of OECs lies in their anti-inflammatory and immunomodulatory functions. They are transplanted into the host to improve the catastrophic inflammatory microenvironment caused by injured nerves, thus promoting the repair and regeneration of injured nerves. The transplantation of OECs into the host can provide good groundwork and support for the repair and regeneration of nerve injury by regulating the activity and infiltration of immune cells, the secretion of inflammatory cytokines and phagocytosis. Therefore, this paper discusses the anti-inflammatory and immunomodulatory mechanisms of OECs transplantation in the repair of nerve injury and the functional role of OECs as an ideal substitute in the treatment of nerve injury.